Era Digital dan Tantangan Non-Industrialis: Pendekatan Manajemen Perubahan dalam Pengembangan Organisasi Berkelanjutan: (Studi Kasus: Transformasi Digital pada Inisiatif Zakat Indonesia (IZI)) - Halimatus Sa'diyah; Jumiati Sasmita (BADAN PENERBIT STIEPARI PRESS, 2025)
The digital era has brought major challenges as well as strategic opportunities for organizations, including non-industrial entities such as zakat institutions. Digital transformation requires organizations to quickly adapt to continuously evolving technologies in order to remain relevant and competitive. Inisiatif Zakat Indonesia (IZI), as a zakat management organization, faces challenges in managing limited digital literacy, human resources, and a still-conventional work culture. This study aims to analyze how a change management approach can support the success of digital transformation in a faith-based non- profit organization. Through the stages of unfreeze, change, and refreeze, IZI has successfully integrated digital technology to enhance the efficiency of zakat collection, improve reporting transparency, and strengthen public trust. This research uses a qualitative approach with a case study on IZI’s digital transformation. The results show that systematic change management plays a crucial role in addressing internal resistance and optimizing the implementation of information technology. These findings serve as an important reference for other philanthropic organizations in implementing sustainable digital transformation focused on improving public services. With the right approach, non-profit organizations can meet the demands of the digital era without compromising the core values that form their foundation.